GOVERNMENTAL REGULATION OF TRANSPORT INFRASTRUCTURE OF THE ECONOMY: IDENTIFICATION OF THE CONCEPTUAL APPARATUS - Iurchenko Ie. O., (Pressing Problems of Public Administration, 2021)
Identification of proper conceptual apparatus of the governmental regulation of transport infrastructure of the economy through research and analysis main categories of conceptual apparatus has been provided by studying the historical aspects of their origin. Relying on listed components transport infrastructure in a number of terms provided “infrastructure”, it enables to define the ’system of transport infrastructure’ as more appropriate to use academically. Numerous definitions of ’infrastructure’ and ’transport infrastructure’ were examined in a narrow sense in terms of both economics and philosophical understanding of all constituent elements that can be considered in. Natural and the newest ones were created by mankind infrastructure elements were not sufficiently reflected in defining of ’transport infrastructure’ term which is used for transportation not only through people’s needs and goods but also information and communication, etc.Clarification of categories and suggested author’s definition the ’governmental regulation of transport infrastructure of the economy’ term is provided and is meant as a purposeful and active influence of public administration system on functioning and developing relationships in transport infrastructure of the economy by applying various mechanisms of public administration. Then, considering the essential aspects proposed definition “governmental regulation of transport infrastructure of the economy”, an interaction of the two systems which are in turn is the subject and object of processes state and public administration, has been noted. Due to each of the systems includes significant number of items, they should be considered systematically and find out some hidden relationships between their elements, especially nowadays, to understanding tangible and intangible assets towards the spread of virtual, digital assets and what, by the way, is of increasing interest in modern states and governments (e.g. Japan, Canada, Germany, Ukraine, Qatar etc.).